GERAKAN KOMUNITAS KEAGAMAAN ONLINE (Melacak Historis Dan Transformasi Dakwah Islam Di Indonesia) - Hopizal Wady; Wely Dozan (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2021)
This article generally examines online religious communities, more specifically this article reviews religious communities in Indonesia with the object of study by the United Muslim community. Muslim United is one of the online religious communities in Indonesia, this community has various kinds of programs including conducting da'wah activities through social media and also a massive alms program at dawn which is carried out with the aim of providing assistance in the form of fruits to class communities. lewd. This article explains specifically about the united Muslim community that exists on social media. The method used in this article is netnography, a method that collects data through the Muslim United Instagram account and also searches for other data from the YouTube, Twitter accounts that are specific about activities in the Muslim United community. The results of this study indicate that the Muslim community is united in opening up hijrah spaces for young people, and carrying out religious social movements for the community without any politics.